PENGARUH GAYA KEPEMIMPINAN DANNBUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN: Studi kasus pada PT.MAKMUR JAYA Surabaya - Morina Irma H.P; Harsono Teguh Santoso; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of leadership style and organizational culture on employee performance with job satisfaction as an at PT. Makmur Jaya Surabaya. The sampling method used is the saturated sampling method. This study uses a saturated sampling technique because the population is relatively small. The sample in this study were employees of PT. Makmur Jaya Surabaya with a total of 30 people. The data used are primary data. The data analysis method used in this study is Multiple Linear Regression with the SPSS 22 application. The results of this study indicate that the independent variables of leadership style, and organizational culture have a significant influence on the dependent variable of employee performance for the results of leadership style having a significant value of 0.00 and culture organization has a value of 0.40 which can be concluded that the significant value of the two X variables is smaller than 0.05 which means that the X variable has a significant effect on performance.